A SYSTEMATIC REVIEW: FACTORS THAT AFFECT THE DEVELOPMENT OF GROSS MOTOR SKILLS OF EARLY CHILDHOOD - Dewi, Ni Putu Diva Ananda Mahatma; Iswhari, Ni Komang Dianda Dhama; Sari, Ni Luh Made Reny Wahyu; Bayantara, I Nyoman Gede; Putra, I Gde Eka (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Gross motor development in early childhood is an important component in children's growth and development, which is closely related to physical, cognitive, social, and emotional abilities. Factors that influence gross motor development include biological factors such as nutritional status and health, as well as external factors such as environmental stimulation, parenting patterns, and early intervention. This study aims to identify and analyze the main factors that contribute to the development of gross motor skills in early childhood and fill the research gap related to the relationship between nutritional status, home stimulation, sleep quality, and technology-based approaches. The research method used was qualitative descriptive with literature study. Relevant scientific articles were analyzed to provide a comprehensive picture of these factors. The results of the study indicated that adequate feeding during the diet transition period, socio-economic conditions, and access to early intervention such as physiotherapy play an important role in gross motor development. In addition, the quality of stimulation at home, good nutritional status, adequate sleep, and the use of technology such as Active Video Games also support the improvement of children's gross motor skills. Consequently, the holistic and multidimensional interventions, including health, nutrition, psychosocial, and technology aspects, are very important in supporting the development of gross motor skills in early childhood. Recommendations are provided for a more integrated and evidence-based intervention approach to support child development.